The Dobbs v. Jackson judgment: a not entirely unforeseeable solution in the abortion litigation in the United States (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article analyzes the decision Dobbs v. Jackson of the US Supreme Court, highlighting the American “exceptionalism” in the abortion regulation issue from a comparative perspective. Moreover, the contribution aims at reflecting on the constitutional impact of the Dobbs judgment, with particular reference to the tensions relating to the separation of powers and the relationship between the representative democratic circuit and the judicial area, which the case – like all previous jurisprudence on the subject – seems to highlight.
Keywords: US Supreme Court; abortion; Roe v. Wade; Dobbs v. Jackson; fundamental rights